2008
DOI: 10.1002/jbm.b.31041
|View full text |Cite
|
Sign up to set email alerts
|

Bone formation and resorption in patients after implantation of β‐tricalcium phosphate blocks with 60% and 75% porosity in opening‐wedge high tibial osteotomy

Abstract: Most of the implanted porous beta-tricalcium phosphate (beta-TCP) can be resorbed. However, beta-TCP block with 75% porosity is inadequate for weight-bearing sites until bone incorporation occurs. Thus, the authors have recently developed beta-TCP block with 60% porosity, which is approximately sevenfold greater in terms of compressive strength than that of beta-TCP with 75% porosity. The authors investigated bone formation and resorption of beta-TCP after implantation in patients of beta-TCP blocks with two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 48 publications
(58 reference statements)
2
53
0
Order By: Relevance
“…It has been reported that β-TCP has excellent osteoconduction and resorbability when filling a bone defect [1][2][3][4][5][6][7][8][9]. With regard to shape, both block and granular forms of β-TCP have been available; however, *Address correspondence to these authors at the Department of Orthopaedic Surgery, NHO Utsunomiya National Hospital, 2160 Shimo-Okamoto, Utsunomiya city, Tochigi, 329-1193 Japan; Tel: +81 28 673 2111; Fax: +81 28 673 9117; E-mail: tanakat@e-utunomiya.hosp.go.jp some cases have presented difficulty in filling irregularly shaped bone defects.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that β-TCP has excellent osteoconduction and resorbability when filling a bone defect [1][2][3][4][5][6][7][8][9]. With regard to shape, both block and granular forms of β-TCP have been available; however, *Address correspondence to these authors at the Department of Orthopaedic Surgery, NHO Utsunomiya National Hospital, 2160 Shimo-Okamoto, Utsunomiya city, Tochigi, 329-1193 Japan; Tel: +81 28 673 2111; Fax: +81 28 673 9117; E-mail: tanakat@e-utunomiya.hosp.go.jp some cases have presented difficulty in filling irregularly shaped bone defects.…”
Section: Introductionmentioning
confidence: 99%
“…The pore density can range between 40% and 60%, with Ca:P stequiometric ratio similar to spongy bone, imitating it (Gautier et al, 1998;Tanaka et al, 2008;Porter et al, 2009). Osteoconduction with calcium phosphate, often used in beta conformation, as beta-tricalcium phosphate (-TCP, CA3(PO4)2), results in resorption of the biomaterial and osseointegration of the treated region in approximately 12 weeks.…”
Section: Bioceramicsmentioning
confidence: 99%
“…The persistence of the biomaterial favors the treatment of cavities resulting from bone resection, filling of osteotomy regions, defects of critical size of the bone (Gaasbeek et al, 2005;Tanaka et al, 2008) The physical properties of -TCP favor its association with liquids such as blood and bone marrow aspirate. In an experimental study with dogs, Bruder and collaborators demonstrated bone formation and the refinement of the bioceramic in association with mesenchymal cells obtained from bone marrow aspirate .…”
Section: Bioceramicsmentioning
confidence: 99%
“…One of the most compre hensively investigated degradable calcium phosphates is βtricalcium phosphate (βTCP) which is proven to be a biocompatible, biodegradable and osteoconductive mate rial [4][5][6]. Besides the choice of the bone replacement mate rial, specific parameters such as, the percentage of porosity [7], the pore size [8] and the interconnectivity [9] are crucial for a complete in-vivo degradation of the bone replacement material. Most studies suggest a pore diameter of 100-1220 µm to ensure adequate degradation, remodelling and vas cularisation [8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies suggest a pore diameter of 100-1220 µm to ensure adequate degradation, remodelling and vas cularisation [8,[10][11][12][13]. Furthermore, the volume percentage of the total porosity should be higher than 60% [7]. Besides the requirement for a specific macroporosity of the ceramic scaffold, a certain percentage of microporosity is important for osteogenesis and the anchoring of the implant to sur rounding bone tissue [14].…”
Section: Introductionmentioning
confidence: 99%